Mengembangkan Tes Bakat untuk Mengenali Bakat dan Potensi Anak Usia Dini - Annisa Tiara Arthamevira Nasution; Azfadina Nur Akmalia; Dik Ulfa Mewangi; Diva Nindias Sahrudin; Erza Khaerunnisa; Siva Nurhaniva (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Early childhood is a "golden age" that is crucial for a child's development, where education plays an important role in optimizing their potential. According to psychologist Dinny H. A. Rully, parents have a significant responsibility in channeling their child's talents from an early age to ensure they do not miss out on this golden period. Developing a child's potential requires a conducive environment and a parenting style that supports creativity, including clear communication and positive parental control. A child's talents can be identified through aptitude tests from an early age, aiming to optimize potential, prevent learning problems, and select appropriate curricula and activities. Internal factors such as motivation and perseverance, as well as external factors like parental support, greatly influence a child's talent development. Aptitude tests, involving child psychologists, encompass various activities to identify types of talents such as intellectual, academic, creative, artistic, psychomotor, and social. Nurturing a child's interests and talents requires attention from parents and the surrounding environment, including providing diverse experiences, motivation, and recognition, as well as offering the necessary resources to overcome obstacles and fully develop the child's abilities.